Diversification of Mangrove Crab Waste into Dimsum and Nugget, for Improving the Economy in Bayeun, East Aceh: Diversifikasi Limbah Kepiting Bakau Menjadi Dimsum dan Nugget, Untuk Meningkatkan Taraf Perekonomian Bayeun Aceh Timur - Syarifah Yusra; Uci Dwi Cahya; Wiwin Apriani (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Diversifying mud crab waste into dimsum and nugget products can increase the economic value of mud crabs cultivated by the Bayeun Geutanyo Forest Farmers (KTH) group in East Aceh. Dimsum and nuggets were chosen because they are foods that are popular with all ages, and can be prepared in a variety of types and flavors. This food can be served in small portions and is considered healthier because it is low in fat. Therefore the cooking process is done by steaming and is rich in protein using crab as the basic ingredient. The aim of this PKM activity is to provide training and knowledge in making dimsum and nuggets to KTH women, as a problem solution for partners, where the selling price of mud crabs which are damaged during harvest is low. The implementation of PKM is carried out in several activity stages, namely: 1) location survey, 2) preparation stage, 3) socialization, 4) training, and 5) monitoring and evaluation. Results of the implementation of this PKM activity, partners have the knowledge and ability to make healthy and delicious dim sum and nuggets, so that they are marketable and can improve the family's economic level. Apart from that, partners receive production equipment that can be used for business continuity so that they can continue to increase their economic income.